Mono- and Bimetallic Au-Cu dendrimer micelle encapsulated nanoparticles as catalysts in the oxidation of styrene. - Kotzé, Gerbrandt (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.